2018
DOI: 10.1002/ejlt.201800058
|View full text |Cite
|
Sign up to set email alerts
|

Oil Uptake by Potato Chips or French Fries: A Review

Abstract: The increase in obesity and fat‐related diseases pose a major health issue especially in developed countries. Over the past years, consumer demand for low‐fat potato chips and French fries has stimulated the scientific work on the issue of fat uptake during frying. The main objective of this review article is to summarize the latest efforts to reduce the oil absorption without deteriorating the organoleptic characteristics, precisely explain the mechanism, frying medium quality, and selection, different parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 126 publications
(149 reference statements)
0
28
0
Order By: Relevance
“…Although the effects of modifying the food surface by pretreatment has demonstrated to reduced oil uptake using the conventional deep frying method, the current technology such vacuum frying and air frying is alternatively becoming a trend in manufacturing low‐fat food (Arslan et al , ; Ayustaningwarno et al , ; Liberty et al , ).…”
Section: Methods In Reducing Oil Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects of modifying the food surface by pretreatment has demonstrated to reduced oil uptake using the conventional deep frying method, the current technology such vacuum frying and air frying is alternatively becoming a trend in manufacturing low‐fat food (Arslan et al , ; Ayustaningwarno et al , ; Liberty et al , ).…”
Section: Methods In Reducing Oil Uptakementioning
confidence: 99%
“…Overall, the economic cost saving of using less oil in both recent technologies is attracting more food industries while meeting the increasing demand for high‐quality, low‐fat food. However, the expensive equipment and higher initial investment could lead to an increase in the cost of fried foods (Arslan et al , ).…”
Section: Methods In Reducing Oil Uptakementioning
confidence: 99%
“…Gamble et al [34] found that oil uptake was closely related to the water loss (R 2 = 0.989) in potato slices in which the oil absorbed by potato slices was found accumulated in the voids left by the water evaporation. When the water bubbles escaped from food materials, they formed capillary pathways and increased the surface porosity [35].…”
Section: Oil Transfermentioning
confidence: 99%
“…However, the voids or capillary pathways are always filled with water during frying and the inner steam pressure may resist oil penetration. Sometimes, the oil is absorbed after the capillary (food material) is removed from the oil [35,37].…”
Section: Oil Transfermentioning
confidence: 99%
See 1 more Smart Citation